Post-traumatic enophthalmos: diagnosis and rehabilitation - M.B. Gushсhina; D.S. Afanasyeva (РМЖ "Клиническая офтальмология")
M.B. Gushchina1, D.S. Afanasyeva2 1Central Research Institute of Dentistry and Maxillo-Facial Surgery, Moscow,  Russian Federation 2 S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Moscow, Russian Federation Post-traumatic enophthalmos is characterized by complex pathogenesis and various clinical manifestations which affect middle facial zone both functionally and esthetically. Occupational and social maladjustment resulting from visual disturbances associated with enophthalmos (i.e., diplopia, restricted ocular motility, ptosis etc.) require early and complete correction of this condition. However, complex anatomy of the orbit and a variety of post-traumatic changes account for the lack of common diagnostic and treatment approaches for the management of patients with orbital trauma. This paper summarizes current approaches to the diagnosis and treatment of post-traumatic enophthalmos and highlights important issues. Further studies are required to develop general diagnostic criteria for post-traumatic enophthalmos and clear indications for surgery. Considering current materials for plastic surgery, surgical techniques for enophthalmos correction, and risk factors for post-traumatic enophthalmos development in the late period, it seems to be important to develop single-step surgical strategy for orbital reconstruction, correction of enophthalmos, and prevention of its further development and/or progression. This paper is based on the data published in the last decade. However, giving the credit to the authors of original materials, we have included earlier publications in the reference list as well. Keywords: orbital trauma, enophthalmos, diplopia, hyaluronic acid; entropion; blepharoptosis; exophthalmometry, lipofilling, silicone implant; titan co nstruction. For citation: Gushchina M.B., Afanasyeva D.S. Post-traumatic enophthalmos: diagnosis and rehabilitation. Russian Journal of Clinical Ophthalmology. 2019;19(4):252–256.